HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI LANJUT USIA MENGUNJUNGI POSYANDU LANSIA - Melawati, Risa; Ma’rifatul Azizah, Lilik (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Posyandu lansia is the elderly health care facility that consists of health care activities which aim to achieve a happy old age and useful life. But in practice, there are still some issues that affect low motivation to participate in Posyandu lansia, one of them is the lack of family social support. This research aims to find out the relationship between social supports of family with motivation of elderly to participate in Posyandu Lansia in Tegalsari Jabon Village Mojoanyar District Mojokerto. This research design is analytic by using cross sectional approach. Population is entire elderly in Tegalsari Jabon Village for about 98 people. Then 47 respondents are taken by using purposive sampling. Independent variable is social supports of family and dependent variable is motivation of elderly to participate in Posyandu Lansia. Data were taken using a questionnaire and then processed and analyzed using the Chi square test with SPSS version 16.0 and the results are presented in the form of frequency distribution tables. Results showed the majority of elderly do not have family support in following Posyandu Lansia for about 30 respondents (63.8%) and most of the elderly have low motivation in following Posyandu Lansia for about 22 respondents (46.8%) and there is a relationship between social supports of family with motivation of elderly to participate in Posyandu Lansia in Tegalsari Jabon Village Mojoanyar District Mojokerto, with p (0.042) < α (0.05). Further, families are expected to increase their support for the elderly to participate in Posyandu Lansia. This could be done in the form of increased elderly motoric development by driving to Posyandu, provide time to deliver the elderly, reminds Posyandu schedule, as well as help with the costs to come to Posyandu.Keywords: social supports of family, motivation of elderly, posyandu lansia